Impacts of Jets and winds from primordial black holes. Issue 1 (25th August 2022) - Takhistov, Volodymyr; Lu, Philip; Murase, Kohta; Inoue, Yoshiyuki; Gelmini, Graciela B
ABSTRACT: Primordial black holes (PBHs) formed in the early Universe constitute an attractive candidate for dark matter. Within the gaseous environment of the interstellar medium, PBHs with accretion discs naturally launch outflows such as winds and jets. We discuss for the first time how PBHs with significant spin can sustain powerful relativistic jets and generate associated cocoons. Jets and winds can efficiently deposit their kinetic energies and heat the surrounding gas through shocks. Focusing on the Leo T dwarf galaxy, we demonstrate that these effects form novel tests and set new limits on PBHs over a significant ∼10 −2 –10 6 M⊙ mass range, including the parameter space associated with gravitational wave observations by the LIGO and VIRGO Collaborations. Observing the morphology of emission will allow to distinguish between jet and wind contributions, and hence establishes a new method for identifying spinning PBHs.